Too much – not enough. The representation of the body and the meaning of symptoms in patients with eating disorders. Issue 2 (2nd July 2016) - Lunn, Susanne; Holm Pedersen, Signe
ABSTRACT: Eating disorders cover different clinical syndromes, all of which are characterized by an immense focus on food, body and weight, an endless attempt to combat the body and by a fluctuation between 'too much and not enough' on different levels (e.g., behaviourally, mentally, physically). The aim of this article is to contribute to the psychoanalytic understanding of eating disorders, to highlight the vital importance of the symptoms as a psychological survival strategy and to illustrate similarities between eating disordered patients as well as the very different pathways that can lead to an eating disorder. Two clinical cases are presented, one very shortly and one in more detail.